Influence of alkyl substitution on the supramolecular organization of thiophene- and dioxine-based oligomers. Issue 3 (9th January 2017) - Zajaczkowski, Wojciech; Nanajunda, Shivananda Kammasandra; Eichen, Yoav; Pisula, Wojciech
Abstract : The influence of the position and geometry of alkyl substituents on the supramolecular organization of thiophene- and dioxine-based oligomers is investigated. Abstract : The interplay between the molecular structure, position and type of alkyl substituents on morphology and molecular packing is essential for the development of high-performance solution-processable organic semiconductors. This study focuses on the influence of the position and geometry of alkyl side chains on the supramolecular organization of thiophene- and dioxine-based oligomers. The structural investigation is performed by X-ray scattering for bulk and thin film samples. It is shown that attaching the side chains at the lateral position of the rigid oligomers mainly results in the formation of one-dimensional stacks. On the other hand, terminal alkyl substitution increases the steric hindrance between side chains and reduces the molecular interactions lowering the sample crystallinity.